Sources and Uses of Funds in State and Local Governments, 1790-1915: (United States) - Sylla, Richard E. ([Verlag nicht ermittelbar], 1993)
This data collection contains information on state government revenues and expenditures between 1790 and 1915. The data were collected in order to categorize revenues and expenditures according to 20th-century census standards. Standard industrial classification (SIC) codes are included.